Some new powdery mildews from Northern India - KAMAL and D.K. AGARWAL, NASIM AHMAD, A.K. SARBHOY (Indian Phytopathology, 2006)
Three new powdery mildews viz. Cystotheca quercina sp. nov., Oidium brassicae sp. nov. and Oidiopsis solani sp. nov. are reported on Quercus incana Roxb., Brassica napus L. var. glauca (Roxb.) Schulz. and Peganum harmala L., respectively for the science from northern India.